2011
DOI: 10.1128/aem.01896-10
|View full text |Cite
|
Sign up to set email alerts
|

Army Ants Harbor a Host-Specific Clade of Entomoplasmatales Bacteria

Abstract: In this article, we describe the distributions of Entomoplasmatales bacteria across the ants, identifying a novel lineage of gut bacteria that is unique to the army ants. While our findings indicate that the Entomoplasmatales are not essential for growth or development, molecular analyses suggest that this relationship is host specific and potentially ancient. The documented trends add to a growing body of literature that hints at a diversity of undiscovered associations between ants and bacterial symbionts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
95
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(101 citation statements)
references
References 55 publications
5
95
1
Order By: Relevance
“…However, previous studies (Funaro et al, 2011) have found that these bacteria are not always present in different subcastes within a single ant colony or different colonies from the same population, indicating that these microorganisms are not essential for the development of the host species. Nevertheless, in certain cases, there is specificity between associated bacteria and ant species.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…However, previous studies (Funaro et al, 2011) have found that these bacteria are not always present in different subcastes within a single ant colony or different colonies from the same population, indicating that these microorganisms are not essential for the development of the host species. Nevertheless, in certain cases, there is specificity between associated bacteria and ant species.…”
Section: Resultsmentioning
confidence: 84%
“…and are known to be present in a number of ant species (Funaro et al, 2011;Ishak et al, 2011;Sapountzis et al, 2015). However, previous studies (Funaro et al, 2011) have found that these bacteria are not always present in different subcastes within a single ant colony or different colonies from the same population, indicating that these microorganisms are not essential for the development of the host species.…”
Section: Resultsmentioning
confidence: 99%
“…Ants (Hymenoptera: Formicidae) are one of the most abundant animal groups (23,25), and microbial symbionts may have facilitated their evolution and diversification (29,55). Recent studies have found a range of putative symbionts in different ant lineages (22,27,28,30,49), and next-generation sequencing techniques are facilitating the endeavor to characterize the microbiome of such arthropod hosts.…”
Section: Discussionmentioning
confidence: 99%
“…Various symbiotic bacterial communities have been described for several ant groups (e.g. Russell et al, 2009;Funaro et al, 2011). Symbiotic bacteria are mainly found in the guts that provide a suitable habitat for a wide range of microbes (Li et al, 2005;Stoll et al, 2007) and play essential roles in the success of herbivorous and fungivorous ants (Davidson et al, 2003;Pinto-Tomas et al, 2009;Russell et al, 2009).…”
Section: Microbial Pathogens Of Myrmica Antsmentioning
confidence: 99%
“…The worker ant surface can also provide a separate microbial niche, which for some ant species has a crucial role in providing antibiotics and fungicides (Little and Currie, 2007) or could generally contribute to protection against disease (Mueller, 2012). While such functional relationships are known for some bacterial groups, the function of many other groups is still poorly understood (Russell et al, 2009;Funaro et al, 2011) and virtually unknown in Myrmica ants.…”
Section: Microbial Pathogens Of Myrmica Antsmentioning
confidence: 99%